Post‐discharge opioid prescribing after laparoscopic appendicectomy and cholecystectomy. Issue 6 (12th May 2020) - Zhao, Jie; Peters, Luke; Gelzinnis, Scott; Carroll, Rosemary; Nolan, Jennifer; Di Sano, Suzanne; Pockney, Peter; Smith, Stephen
Abstract: Background: Opioid over‐prescription following surgery is a significant public health issue in most developed countries. Multiple studies have been conducted in the USA demonstrating and investigating the issue; however, there is a lack of literature addressing this topic in the Australian setting. The aim of this study is to review prescribing practices at an Australian tertiary referral hospital on discharge in patients having undergone laparoscopic cholecystectomy (LC) or laparoscopic appendicetomy (LA). Additionally, to identify potential factors which influence medical officer prescribing practices. Methods: A retrospective observational study on opioid prescribing practice on all patients who underwent LC or LA over a 12‐month period at an Australian tertiary referral hospital. Results: A total of 435 patients (223 LC, 214 LA) were prescribed a mean opioid dose on discharge of 25 oral morphine milli‐equivalents (range 0–180 morphine milli‐equivalents). Less opioids were prescribed following elective procedures (42% versus 10%, P  < 0.001). There is a downward trend of opioid prescribing on discharge as the Junior Medical Officer clinical year progresses ( P < 0.001). Conclusions: This study demonstrates a lower rate of opiate prescription on discharge for LC and LA in an Australian setting when compared to the US data. There is a wide diversity of prescribing demonstrated. This indicates the need for better training of opioid prescribers to reduce over‐prescribing. Abstract : Opioid over‐prescription, following surgery, is a significant public health issue in most developed countries. This study demonstrates a lower rate of opiate prescription on discharge for laparoscopic cholecystectomy and laparoscopic appendicectomy in an Australian setting when compared to US data. The urgency of the procedures and the experience of the prescriber also had an impact on opioid prescriptions. Increasing experience of the prescribing doctor appears to be correlated to decreased amounts of opioid prescribed.